2019
DOI: 10.1161/circheartfailure.119.006635
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Patterns in Temporary Mechanical Circulatory Support for Shock in the Critical Care Cardiology Trials Network (CCCTN) Registry

Abstract: Background: Temporary mechanical circulatory support (MCS) devices provide hemodynamic assistance for shock refractory to pharmacological treatment. Most registries have focused on single devices or specific etiologies of shock, limiting data regarding overall practice patterns with temporary MCS in cardiac intensive care units. Methods: The CCCTN (Critical Care Cardiology Trials Network) is a multicenter network of tertiary CICUs in North America. Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 16 publications
5
41
0
Order By: Relevance
“…With the exception of the IMPRESS-in-Severe-SHOCK trial, which included younger patients, the age of included patients in previous RCTs of active MCS was similar to the present study [14,[22][23][24]. On the other hand, previous cohort studies showed a lower age of patients receiving active MCS, which might be due to selection bias [17,27,31,32]. The shock index, which was identified as a strong outcome predictor in STEMI patients, was higher in patients receiving active MCS [33].…”
Section: Clinical Characteristics and Rates Of Mcs Implementationsupporting
confidence: 75%
See 2 more Smart Citations
“…With the exception of the IMPRESS-in-Severe-SHOCK trial, which included younger patients, the age of included patients in previous RCTs of active MCS was similar to the present study [14,[22][23][24]. On the other hand, previous cohort studies showed a lower age of patients receiving active MCS, which might be due to selection bias [17,27,31,32]. The shock index, which was identified as a strong outcome predictor in STEMI patients, was higher in patients receiving active MCS [33].…”
Section: Clinical Characteristics and Rates Of Mcs Implementationsupporting
confidence: 75%
“…These devices, among others, include the microaxial flow pumps from the Impella ® family, the TandemHeart ® and ECMO [6]. Although frequently used in clinical routine, data supporting a prognostic benefit with active MCS devices in infarct-related CS are limited [14][15][16][22][23][24][25][26][27][28][29][30]. The aim of the present analysis was to investigate the prognostic role of active MCS devices rather than an outcome analysis of patients treated with IABP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked about information about changes in adolescent reproductive health, there were significant differences, found that 60.56% were; "Sometimes, but uncomfortable" "Sometimes I talk about other things" "Always, even if I avoid" "Always, when I'm happy" "Never (because of shame and confusion)" "Never (because of my secret)" "There's no use for me to tell (you don't understand)" "About weight gain" "Maybe for the current era promiscuity has become something that is often done, but as teenagers, we must have a firm principle to reject it" [10]Kessler RC, Angermeyer M, Anthony JC, Berg [11] states that adolescence is an important period in developing and maintaining social and emotional habits that are important for mental health. These conditions include adopting a healthy sleep pattern; do regular exercise; develop coping, problem-solving, and interpersonal skills, including learning to manage emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 34% of patients in a multicenter network of tertiary cardiac intensive care units in North America were managed with a mechanical device in the intensive care unit. 23 The critical care team managing these patients will need to understand the various forms of mechanical support. As new devices are introduced, topics, such as anticoagulation, device placement, and appropriate pressure/flow monitoring, will need to be discussed during multidisciplinary daily rounds.…”
mentioning
confidence: 99%